FACTORS OF HOSPITAL BYLAWS IMPLEMENTATION IN INDONESIA (SCOOPING REVIEW) - Danasti, Zulfa Nadia; Aini, Qurratul (Universitas Aisyah Pringsewu, 2024)
The implementation of Hospital Bylaws has different patterns and character, depending on the background and underlying factors. This study was aimed to examine the factors that influence the implementation of hospital bylaws in Indonesia. The research design used in this article was scoping studies. This research used article data obtained through a systematic search through two methods, namely systematic database search and systematic manual search. From the entire article that has been reviewed, it was found that the implementation of hospital bylaws was based on 4 factors, namely the owner, director, medical staff, and juridical. Factors that affected the implementation of hospital bylaws from the owner dimension are knowledge, awareness, and supervision about the implementation of hospital bylaws. Factors that affected the implementation of hospital bylaws from the Director Dimension were in the form of supervision and management of medical staff on the implementation of hospital bylaws. Factors that affected the implementation of hospital bylaws of the medical staff dimension was in the form of patient safety. The last factor that influences the implementation of hospital bylaws is the regulation on hospital bylaws, namely the Permenkes No: 75/MENKES/PER/IV/2011 which regulates hospital bylaws.